Analisis Relasi Sosial dan Ekonomi Pedagang dengan Bank Keliling di Pasar Tradisional - Najua Syahrani; Lesti Heriyanti; Ayu Wijayanti (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
Traditional markets are economic spaces that allow for direct negotiations between sellers and buyers to meet daily needs such as household goods, agricultural products, and seafood. In this context, mobile banks serve as an alternative source of capital for small traders who have difficulty accessing formal financial institutions. This research was conducted in Pasar Minggu, Bengkulu City, with the aim of analyzing the social and economic relationships between traders and mobile banks. The study employed dependency theory and a qualitative approach to understand the unequal economic relationship patterns resulting from the inferior position of traders who rely on financial resources from mobile banks. Data were collected through unstructured interviews, two months of observation, and documentation, using a purposive method for selecting informants. The results revealed four main findings: money lending practices among Pasar Minggu traders, the role of trust in lending, information dissemination patterns about mobile banks, and the emergence of financial dependence on mobile banks. The study concluded that although mobile banks play a role in assisting small businesses with capital, the resulting relationship patterns actually create long-term economic dependence for the traders.